Pemberdayaan Keluarga Terhadap Dukungan Menyelesaikan Pengobatan TB Paru di Puskesmas Medan Johor Tahun 2024 - Martaulina Sinaga; Lisbet Gurning; Sri Mulati Nendah; Deo Cristian Meliala; Emma Lumbantoruan (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Pulmonary tuberculosis (TB) is an infectious disease that requires long-term treatment and patient compliance so that the healing process can be achieved properly. One of the factors that plays an important role in the success of pulmonary TB treatment is family support. Families who are directly involved in care and motivation can increase the patient's enthusiasm to complete treatment. Therefore, empowering families in supporting pulmonary TB treatment is very important to reduce the number of failed treatments and prevent drug resistance. This community service aims to empower families in providing effective support to pulmonary TB patients so that patients can complete their treatment completely. The empowerment program carried out through counseling on the importance of adherence to TB treatment, as well as training on how to care for patients and reduce social stigma against TB, is expected to increase the active role of families in supporting patient treatment. This community service activity involves families of pulmonary TB patients, medical personnel, and the surrounding community, with an educational and collaborative approach. The results of this community service show an increase in family understanding of TB disease, the importance of adherence to treatment, and a reduction in stigma against TB patients. In addition, families feel more prepared and motivated to support patients in undergoing treatment. Family empowerment has been proven effective in increasing the completion rate of pulmonary TB treatment, which in turn can reduce transmission rates and drug resistance.